Protective role of CFTR during fungal infection of cystic fibrosis bronchial epithelial cells with Aspergillus fumigatus - Illek, Beate; Fischer, Horst; Machen, Terry E.; Hari, Gopika; Clemons, Karl V.; Sass, Gabriele; Ferreira, Jose A. G.; Stevens, David A. (Frontiers in Cellular and Infection Microbiology, 2023)
Lung infection with the fungus Aspergillus fumigatus (Af) is a common complication in cystic fibrosis (CF) and is associated with loss of pulmonary function. We established a fungal epithelial co-culture model to examine the impact of Af infection on CF bronchial epithelial barrier function using Af strains 10AF and AF293-GFP, and the CFBE41o- cell line homozygous for the F508del mutation with (CF+CFTR) and without (CF) normal CFTR expression. Following exposure of the epithelial surface to Af conidia, formation of germlings (early stages of fungal growth) was detected after 9-12 hours and hyphae (mature fungal growth) after 12-24 hours. During fungal morphogenesis, bronchial epithelial cells showed signs of damage including rounding, and partial detachment after 24 hours. Fluorescently labeled conidia were internalized after 6 hours and more internalized conidia were observed in CF compared to CF+CFTR cells. Infection of the apical surface with 10AF conidia, germlings, or hyphae was performed to determine growth stage-specific effects on tight junction protein zona occludens protein 1 (ZO-1) expression and transepithelial electrical resistance (TER). In response to infection with conidia or germlings, epithelial barrier function degraded time-dependently (based on ZO-1 immunofluorescence and TER) with a delayed onset in CF+CFTR cell monolayers and required viable fungi and apical application. Infection with hyphae caused an earlier onset and faster rate of decline in TER compared to conidia and germlings. Gliotoxin, a major Af virulence factor, caused a rapid decline in TER and induced a transient chloride secretory response in CF+CFTR but not CF cells. Our findings suggest growth and internalization of Af result in deleterious effects on bronchial epithelial barrier function that occurred more rapidly in the absence of CFTR. Bronchial epithelial barrier breakdown was time-dependent and morphotype-specific and mimicked by acute administration of gliotoxin. Our study also suggests a protective role for CFTR by turning on CFTR-dependent chloride transport in response to gliotoxin, a mechanism that will support mucociliary clearance, and could delay the loss of epithelial integrity during fungal development in vivo.